Gethuk Tular Sebagai Strategi Komunikasi Lokal Dalam Mempromosikan Desa Wisata Batik Girilayu - Fada, Hawa La’ala Nabilla; Farhah, Eva (JURNAL DESTINASI PARIWISATA, 2024)
The aim of this research is to explain the application of the Gethuk Tular communication pattern as a media for promoting local communication in the Girilayu batik tourism village. Research opens knowledge about strong relationships between various parties in the form of effective communication. Gethuk Tular as an asset in understanding the concept of communication as a tool to achieve better results in various situations. The method used in this research is a qualitative method with a case study approach. The case study in this research is a problem in the Girilayu Batik Tourism Village, which is a unique study and has certain criteria. The data sources in this research are primary and secondary data sources. The primary data source in this research is the results of interviews with informants, while the secondary data source in this research is references from tourism promotion literature, innovation diffusion literature in communication, journal literature regarding Gethuk Tular communication and other supporting media. The sampling technique uses purposive sampling. The samples selected had criteria including local community managers of the Girilayu Batik Tourism Village, batik craftsmen, and members of the Pokdarwis. The data analysis technique used has several stages, namely data collection, reduction and data presentation. The results of this research show that Gethuk Tular's communication strategy strategy which involves interaction between tourist village managers and other tourist village managers, relationships with consumers, and relationships in education and employment of local communities has an important role in expanding the promotional reach of the Girilayu Batik Tourism Village. Using the theory of diffusion of innovation and communication patterns can increase visibility and attractiveness as a tourist destination. Keywords: Tourism Promotion, Gethuk Tular Communications, Diffusion of Innovation.